2020
DOI: 10.7717/peerj.10022
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of Hsp70/110 genes in rainbow trout and their regulated expression in response to heat stress

Abstract: Heat shock proteins (Hsps) play an important role in many biological processes. However, as a typical cold water fish, the systematic identification of Hsp70/110 gene family of rainbow trout (Oncorhynchus mykiss) has not been reported, and the role of Hsp70/110 gene in the evolution of rainbow trout has not been described systematically. In this study, bioinformatics methods were used to analyze the Hsp70/110 gene family of rainbow trout. A total of 16 hsp70/110 genes were identified and classified into ten su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 70 publications
(80 reference statements)
2
10
0
Order By: Relevance
“…With increasing temperature, almost all of these genes had significantly and continuously upregulated expression, and the number of DE HSP70 genes was clearly increased. Similar results have also been found in the L. maculatus and O. mykiss , in which most of the examined HSP70 genes showed significantly upregulated expression in different tissues after exposure to heat stress [ 18 , 22 ]. Moreover, four significantly upregulated HSP70 genes in both kidney and liver tissues were identified, hsp70 ( hspa1a ), hspa1b , hspa5 , and hspa8a.1 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With increasing temperature, almost all of these genes had significantly and continuously upregulated expression, and the number of DE HSP70 genes was clearly increased. Similar results have also been found in the L. maculatus and O. mykiss , in which most of the examined HSP70 genes showed significantly upregulated expression in different tissues after exposure to heat stress [ 18 , 22 ]. Moreover, four significantly upregulated HSP70 genes in both kidney and liver tissues were identified, hsp70 ( hspa1a ), hspa1b , hspa5 , and hspa8a.1 .…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, 14 HSP70 genes have been detected in the Cynoglossus semilaevis through database searches and by manual selection, and expression profiles have demonstrated that most of these gene family members, especially hspa5, showed upregulated expression after exposure to low-salinity stress [ 21 ]. Moreover, a total of 16 HSP70 genes were detected in the genome of the rainbow trout ( Oncorhynchus mykiss ); in addition, an RNA-seq analysis indicated that 4 and 7 HSP70 gene family members showed significantly upregulated expression after heat stress in liver and head kidney tissues, respectively [ 22 ]. In the channel catfish ( Ictalurus punctatus ), 16 HSP70 genes were detected via a combination of genome databases and RNA-seq data, and 9 and 2 gene family members showed significant expression in gill tissue after a challenge with the Flavobacterium columnare and in intestine tissue after infection with the Edwardsiella ictaluri [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the increasing number of available genomic resources, more and more HSP90 genes and HSP70 genes have been discovered in teleost species, and their potential involvement under environmental stresses have been investigated by examining the gene expression changes. For example, a total of 8 HSP90 and 16 HSP70 genes were identified in rainbow trout ( Oncorhynchus mykiss ), respectively ( Ma et al, 2020 ; Ma and Luo, 2020 ). The significantly differential expressions of six HSP90 genes and four HSP70 genes in the liver, and six HSP90 genes and six HSP70 genes in the head kidney were reported after heat stress treatment, indicating they may take part in heat stress response in rainbow trout ( Ma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 No. 4 (2021) Received: 29.05.2021 -Accepted: 26.06.2021 2265 Heat shock proteins (70 HSP) molecular chaperones that are stimulated when the body is exposed to stress and that these proteins have an important role in the immune response against pathogens, including the parasite Giardia, as these proteins work to preserve the functions of proteins by helping amino acid chains to fold in their correct protein shape and remove damaged proteins, and they also display the antigen by delivering antigens Peptide to class 1 histocompatibility complex (MHC), which is found on the surface of cells (Ma and Luo, 2020). The defense against infection with the Giardia parasite is localized because the parasite does not attack the epithelial layer and is characterized by relatively little or no mucosal infection (Li, 2004), as the immune response is important to eliminate the parasite during the infection stage, because interleukins are proteins produced by lymphocytes and monocytes, and some of them are produced by Peyerspatches CD4 + cells or by lymphatic tissues associated with the mucous layer, which leads to Stimulation of longacting antigen or cystic stage G parasite.…”
Section: Heat Shock Protein (70 Hsp Heat Sock Proteins (Hsp70)mentioning
confidence: 99%